A sequence-specific DNA binding small molecule triggers the release of immunogenic signals and phagocytosis in a model of B-cell lymphoma. Issue 4 (16th July 2015) - Kang, JeenJoo S.; Dervan, Peter B.
Abstract: Means to cause an immunogenic cell death could lead to significant insight into how cancer escapes immune control. In this study, we screened a library of five pyrrole–imidazole polyamides coding for different DNA sequences in a model of B-cell lymphoma for the upregulation of surface calreticulin, a pro-phagocytosis signal implicated in immunogenic cell death. We found that hairpin polyamide1 triggers the release of the damage-associated molecular patterns calreticulin, ATP and HMGB1 in a slow necrotic-type cell death. Consistent with this signaling, we observed an increase in the rate of phagocytosis by macrophages after the cancer cells were exposed to polyamide1 . The DNA sequence preference of polyamide1 is 5′-WGGGTW-3′ (where W = A/T), indicated by the pairing rules and confirmed by the Bind-n-Seq method. The close correspondence of this sequence with the telomere-repeat sequence suggests a potential mechanism of action through ligand binding at the telomere. This study reveals a chemical means to trigger an inflammatory necrotic cell death in cancer cells.